Tindakan proaktif mahasiswa KKM UIN Malang dalam membiasakan PHBS: Langkah awal pencegahan stunting di MTs Almaarif 02 Singosari Malang - Indriansyah, Renata Tiand; Salima, Syirtu Fillaili; Zaida, Nur Aisya Jaffa; Aulia, Ahmad Fikri; Aghna, Naula Sulma; Syidad, Ahmad Wildan; Firdausi, Mutiara; A'yuninah, Kholidah Qurrota; Wakindiyah, Nimas Yuhyih; Fitriani, Hanifah (Maliki Interdisciplinary Journal, 2024)
Proactive actions taken by the Student Scientific Group (KKM) of UIN Malang in spreading awareness about stunting and the importance of Clean and Healthy Living Behaviors (CHLB) began with early prevention steps at MTs AlMaarif 02 Singosari, Malang. Stunting, a linear growth disorder resulting from chronic malnutrition or chronic infectious diseases, carries significant short-term and long-term impacts. Risk factors for stunting include genetic aspects, susceptibility to diseases, nutritional status, family income, maternal education, and limited healthcare services. Data from the Indonesian Ministry of Health's Survey on Nutritional Status (SSGI) indicates a high prevalence of stunted children in East Java, reaching 19.2% in 2022, ranking this province as the 25th highest nationwide. Therefore, this community engagement aims to enhance students' understanding through health education on stunting and its preventive measures, particularly through CHLB. Health education activities are delivered to 40 students using lecture methods followed by discussions, Q&A sessions, and milk distribution. The research method employed in this study is a literature review utilizing Google Scholar and PubMed as sources for article searches.